¿Puede el Perú llegar a ser desarrollado en una generación? Oportunidades y obstáculos para lograrlo - Rivera, Iván (2011)
Can we become a developed country in a generation? Yes, if we implement the following reforms. Sustain macroeconomic stability. Sustain commercial and financial openness to become the source of sustained economic growth. Complement openness with the following reforms: improvements in human capital via increases in the quality of education and health, increase in private investment via improvement in the investment climate and complementary infrastructure, financial deepening and labor market reform. A new source of growth is the promotion of a broad entrepreneurial middle class via the elimination of the distortions in the productive structure that have induced the increase of informality and the concentration of entrepreneurship in microenterprises and in a low productivity services sector. The elimination of distortions in the tax system, the social security system and the labor market will increase the demand for quality labor and the improvements in human capital will increase its supply and induce the emergence of a broad entrepreneurial middle class. Finally, for this entrepreneurial middle class to emerge, we have to reform the estate to eradicate corruption, reduce crime and to create a predictable and fair judicial system to defend property rights including compliance with commercial contracts.